Assessment of vertebrate diversity in Sherpur Reserve Forest, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2025)
Bangladesh is known for its rich biodiversity and wide variety of animal species. Identifying these species and understanding their abundance is a critical step in conserving its biological flora and fauna. Detailed knowledge of each species and its ecological requirements are essential for effective conservation efforts. In this context, the present study was conducted in Mymensingh's Sherpur Reserve Forest from November 27, 2023 to March 11, 2024 employing methods such as field observation, questionnaires and community-based approaches for data collection. The study revealed an impressive diversity of species, including 22 species of fishes, 13 amphibians, 16 reptiles and 11 mammals. The Simpson’s Diversity Index demonstrated high levels of diversity across these groups, with amphibians scoring 97%, fish 93%, reptiles 84% and mammals 77%. This investigation not only highlights the faunistic variety of Sherpur Reserve Forest and its surroundings but also aids in identifying key faunal elements of high conservation significance and assessing their potential risk of extinction. As preserving biological diversity remains Bangladesh's top environmental priority, the findings of this study will play a pivotal role in guiding future conservation strategies.J. biodivers. conserv. bioresour. manag. 10(2), 2024: 79-86